‘Things Will Look Up Because They Always Do’: The Continuation of My Autoethnography as a Self-Directed Learner of French - Robert J. Werner (Studies in Self-Access Learning Journal, 2020)
This is the second part of an autoethnography about trying to enrich my vocabulary and improve my listening skills as a self-directed learner through French language songs. I followed the same Study Use Review Evaluate (SURE) learning cycle as my students in a self-access English class, and my work occurred at the same time as theirs, over a period of six weeks. Throughout the project and in the course of writing it up, I was making comparisons and identifying connections between my learning and that of my students. This installment covers the second and third weeks of the project, and part of the fourth. First, it discusses vocabulary, describes how I adjusted a strategy, ways I enlisted help from native French speakers, and a problem that arose with using new words (the second step of SURE). Next, it details how I reviewed grammar through Duolingo, a language learning app, and the unexpected benefits I derived from using this app. Finally, this paper examines fluctuations in motivation and affect, which many learners experience at some point, and this initially led to anxiety and self-doubts about my purpose in conducting this project. Stepping into the learner’s experience was valuable, however, in helping me to rediscover intrinsic motivation and regain my self-confidence as I headed into the final weeks of the project.